About the Contributors - ⠀, — (The Archive; Vol 4 No 1–2 (2023): Regular Issue Vol. 4, Nos. 1–2, 2024)
Kritsana Athapanyawanit Canilao is an Assistant Professorial Fellow at the Department of Linguistics, College of Social Sciences and Philosophy, University of the Philippines Diliman. She earned her PhD in Linguistics at Research Institute for Languages and Cultures of Asia (RILCA), Mahidol University, Thailand. She is currently working on Standard Thai tone production of Filipino speakers. This study aims to find practical methods and tools for guiding learners to produce and apply Thai distinctive tones communicatively.   Dustin Matthew O. Estrellado  is a licensed professional librarian at the Rizal Library Loyola, Ateneo de Manila University. He works as an indexer and a librarian at the Filipiniana Section and Indexing Pool where he organizes Filipiniana materials and helps in its collection development and management. His former work includes cataloging, describing, and organizing the Ernesto Constantino Legacy Materials at the UP Department of Linguistics Library in which the Philippine Linguistics raw data are included. His research interests include information literacy, collection management, and archival studies.   Elsie Marie Or  is an assistant professor at the University of the Philippines Diliman Department of Linguistics where she teaches linguistics and Chinese Mandarin. Her research interests include language documentation and description, the interface between form and meaning, and language acquisition, particularly among adults and heritage language learners. She currently supervises the cataloging and digitization of the legacy language materials in the Ernesto Constantino Collection.   Ma. Mercedes G. Planta , Professor of History at the University of the Philippines Diliman (UPD), specializes in the history of medicine in colonial Southeast Asia. Her book,  Traditional Medicine in the Colonial Philippines, 16th to the 19th Century (2017), received the Best Book in Science Award from the National Book Awards of the Philippines in 2018 and was a finalist for the Best Book in History by the Filipino Readers' Choice Award of the Book Development Association of the Philippines in 2022. In 2019, Dr.~Planta was honored with the title of University Scientist I by the University of the Philippines System for her significant contributions to science and technology and her scientific productivity. She currently chairs the History and Geography Section of the Social Sciences Division, National Research Council of the Philippines (NRCP). Contact her at mgplanta@up.edu.ph.   Arwin Mesina Vibar  obtained his MA English Studies and PhD Linguistics degrees from the University of the Philippines Diliman while teaching at the University of the Philippines Manila and later at the University of Asia and the Pacific as an Assistant Professor. In 2017--2019 he served as an affiliate Professor at the Widya Mandala Surabaya Catholic University in Indonesia and in 2021 was invited to teach a special course on Missionary Linguistics at the University of Santo Tomas Graduate School. He returned to the University of the Philippines Manila (UPM) as an Associate Professor and now serves as Chair of the Department of Arts and Communication at the UPM College of Arts and Sciences. He teaches Linguistics, Spanish, and Communication courses.